Development of the recombinant Semliki Forest virus vector as a gene therapy agent for the central nervous system - Jerusalmi, Alan (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2004)
Multiple sclerosis (MS) is a neurological disease of the central nervous system (CNS), and a major cause of disability in young adults. It is characterized by the presence of inflammatory infiltrates containing autoreactive T cells, resulting in demyelination and axonal loss within the CNS. One of the greatest challenges in the treatment of MS is to get the therapeutic agent to successfully cross the bloodrbrain barrier, and exert an activity inside the CNS.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin